PENGGUNAAN DEIKSIS DALAM KUMPULAN CERPEN BH KARYA EMHA AINUN NADJIB - Sinta, Sinta; Patriantoro, Patriantoro; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was latinned by the desire to find, form, meaning of leksikal, and semantic function, deiksis person, deiksis place, and the time in the form shrot story of Emha Ainun Nadjib. This study is designed to describe the form, the meaning of leksikal, and the semantic function of the deiksis person, deiksis place, and the deiksis of the time found in the form a collection of shrot story BH by Emha Ainun Nadjib. Researchers are using qualitative forms of descriptive method in doing this research. The data in this study is the deiksis persona, the deiksis of the place, and the deiksis of the time that is found in the short story. The source of the data in this study is 23 short stories in the by of Emha Ainun Nadjib. Data collection techniques in this study using a documentary technique. The instrument of this study is done by taking notes of data which are the sentences that contain deiksis person, the deiksis place, and the deiksis of time.Key word: Pragmatic, Use of Deiksis